An Investigation of Factors Increasing the Risk of Aggressive Behavior among Schizophrenic Inpatients - Lejoyeux, Michel (Frontiers in Psychiatry, 2013)
Aim of the study This study tried to identify risk factors of aggressive behavior in a population of schizophrenic inpatients. We tested the association between aggressive behavior and socio-demographic characteristics, addictive disorders, history of suicide attempt and sexual violence, impulsivity and sensation seeking. Methods All consecutive schizophrenic inpatients (100) were assessed during six months. Aggressive behavior was quantified with a standardized scale, the Overt Aggression Scale (OAS). We studied socio-demographic characteristics and the history of suicide attempt and sexual violence with a specific standardized questionnaire. Addictive disorders were identified with the Fagerström and CAGE questionnaires and with the DSM-IV-R diagnostic criteria for nicotine, alcohol, cannabis opiates, and cocaine abuse and dependence disorders. Lastly, we studied sensation-seeking with the Zuckerman scale and impulsivity with the Barratt scale. Results Linear regression identified four factors associated with aggressive behaviour: male gender (odd ratio =12.8), history of sexual violence (odd ratio = 3.6), Fagerström score (odd ratio= 1.3), number of cigarettes smoked each day (odd ratio=1.16). Patients with nicotine use or dependence had significantly higher levels of OAS scores. This difference was not observed between patients with or without alcohol dependence. OAS scores were correlated to the number of cigarettes smoked each day and to Fagerström scores. Patients with a higher level of sensation seeking and impulsivity also had higher OAS scores. Conclusion A Typical schizophrenic patient at risk of showing aggressive behavior is a man, who smokes and presents a history of sexual violence.